Comparison of Glucose Insulin Model for Artificial Pancreas: Comparison of glucose-insulin model - Umer Saleem, Muhammad; Farman, Muhammad; Meraj, M. A.; Tabassum, M.F. (Proceedings of the Pakistan Academy of Sciences: A. Physical and Computational Sciences, 2021)
The controllability and observability of a glucose-insulin system are checked for Bergman’s minimal model, Sandhya model, Hovorka model, Sturis Tolic model and their modified form for a type 1 diabetic patient. These models are to simulate the glucose-insulin system for the treatment of type 1 diabetes mellitus. Models take the only insulin as input and glucose as an output. A control system can only be used in the form of closed-loop control to stabilize the system. It would enable diabetic patients to control their disease. Currently, no fully automated artificial pancreas is available. Comparison of controllability and observability are measured for this purpose. These models can be used to simulate a glucose-insulin system for the treatment of type 1 diabetes. This may play an important role in the development of the fully automatic artificial pancreas and stabilize the control loop system for the Glucose Insulin pump.